Heteroatom-doped carbonaceous electrode materials for high performance energy storage devices. Issue 7 (23rd April 2018) - Shah, Afzal; Zahid, Anum; Subhan, Hanif; Munir, Azeema; Iftikhar, Faiza Jan; Akbar, Muhammad
Abstract : Heteroatom-doped carbons are attractive materials for efficient energy generation as these can catalyse reactions in high performance energy devices. Abstract : The development of cost affordable and efficient catalysts for speeding up electrode reactions is key for boosting up the commercial viability of fuel cells, metal air batteries and other energy production and storage devices. Although state-of-the-art platinum demonstrates excellent performance as an electrode material, its susceptibility to poisoning, high cost and limited availability have blocked the road for large scale commercialization of Pt based energy conversion/storage devices. In this connection carbon nanomaterials are attractive choices on account of their corrosion resistant properties, affordable cost, widespread availability, unique surface features, environmentally acceptable nature and practical capability for addressing the global energy challenge. Moreover, the catalytic role of carbon nanomaterials is expected to be further upgraded by the incorporation of dopants into their framework. Hence, the current review article is at the heart of underlining the recent progress achieved under the umbrella of heteroatom-doped carbons to accelerate reactions in advanced energy generation devices.